Ta có :
\(A=\frac{x-2}{3x+2}\)
a) \(A=0\Leftrightarrow\frac{x-2}{3x+2}=0\)
\(\Leftrightarrow x-2=0.\left(3x+2\right)\)
\(\Leftrightarrow x-2=0\)
\(\Leftrightarrow x=2\)
b) \(A< 0\Rightarrow\frac{x-2}{3x+2}< 0\)
\(\Rightarrow\)\(x-2< 0\) ; \(3x+2>0\) hoặc \(x-2>0\) ; \(3x+2< 0\)
\(\Rightarrow\)\(x< 2\); \(3x>-2\) hoặc \(x>2\) ; \(3x< -2\)
\(\Rightarrow\)\(x< 2\); \(x>\frac{-2}{3}\) hoặc \(x>2\) ; \(x< \frac{-2}{3}\)
\(\Rightarrow\frac{-2}{3}< x< 2\) hoặc \(x\in\varnothing\)
Vậy \(-\frac{2}{3}< x< 2\) thì \(A< 0\)